Manfaat Sari Mentimun untuk Pengobatan Hipertensi di RT 04 Kelurahan Bagan Pete Kecamatan Alam Barajo Kota Jambi - Yuliandani Yuliandani; Yuli Yanti; Umi Halimatusa’diyah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
High blood pressure or hypertension is a degenerative disease and can result in a risk of death. The heritage of the archipelago in traditional medicine that has been carried out by our ancestors or forefathers has been widely imitated by the community. They have the ability to process family plants into medicinal ingredients. People are used to using natural medicinal preparations and increasingly believe in their health benefits. Based on the survey results obtained from the people of Rt 04 Bagan Pete, there is a disease that is often suffered, namely hypertension. One, treatment therapy for hypertension is cucumber fruit which is processed into cucumber juice. The content contained in cucumbers such as potassium, magnesium and phosphorus can treat hypertension. Based on the community service activities that have been carried out at RT.04, Bagan Pete Village, Alam Barajo District, Jambi City, it can be concluded that the knowledge and understanding of the community in RT.04 has increased after counseling was carried out.